Abraham "Sahabat Allah" dalam Tawarikh 20:7 sebagai Ingatan Budaya - Adi, Hery Setyo (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2025)
"Abraham, your friend"—a title that appears in 2 Chronicles 20:7—holds deep theological significance for the post-exilic people of Judah. This article presents a study of that title using the cultural memory method developed by Jan Assmann alongside the historical-critical method. The findings reveal that the mention of Abraham as God’s friend in King Jehoshaphat’s public prayer serves as a means of reactivating the collective memory of Judah’s communal identity and theological foundation in the face of crisis. The redaction of the Book of Chronicles during the Persian post-exilic period demonstrates that the memory of Abraham as God’s friend functioned both as foundational memory and contra-present memory to build identity, generate hope, and strengthen the legitimacy of Judah’s post-exilic existence. The memory of Israel as the descendants of Abraham, the friend of God, shaped a collective identity that distinguished Israel from other nations and affirmed their spiritual claim to the Promised Land, despite their political subjugation under Persian rule. The contemporary implication of this study offers a theological perspective for Christian communities to uphold their faith identity amid pressure through spiritual strategies such as theological memory, perseverance in prayer, and nonviolent resistance. Abstrak “Abraham, sahabat-Mu,” sebuah julukan yang muncul dalam 2 Tawarikh 20:7, memiliki makna teologis yang mendalam bagi bangsa Yehuda pascapembuangan. Artikel ini merupakan hasil studi mengenai julukan tersebut dengan menggunakan metode ingatan budaya yang dikembangkan Jan Assmann dan metode kritik historis. Temuan menunjukkan bahwa penyebutan Abraham sebagai sahabat Allah dalam doa publik Raja Yosafat merupakan sarana mengaktifkan ingatan masa lalu tentang identitas komunal dan dasar teologis keberadaan bangsa Yehuda untuk menghadapi situasi krisis. Peredaksian kitab Tawarikh pada masa pascapembuangan periode Persia memperlihatkan ingatan tentang Abraham sahabat Allah sebagai foundational memory dan contra-present memory sekaligus guna membangun identitas, menciptakan harapan, dan memperkuat legitimasi keberadaan Yehuda pascapembuangan. Ingatan tentang Israel, keturunan dari Abraham yang adalah sahabat Allah, juga membentuk identitas kolektif untuk membedakan Israel dari bangsa-bangsa lain, serta meneguhkan klaim spiritual atas tanah perjanjian meskipun secara politis berada di bawah kekuasaan Persia. Implikasi kontemporer dari kajian ini memberikan pandangan teologis bagi komunitas Kristen untuk mempertahankan identitas imannya di tengah tekanan, melalui strategi spiritual, yakni ingatan teologis, ketekunan berdoa, dan tidak melakukan perlawanan secara fisik.